Variabel-variabel yang Memengaruhi Total Factor Productivity Industri Pengolahan di Kawasan Barat Indonesia Tahun 2011-2019 - Agustien Wahyuningsih; Budyanra Budyanra (Politeknik Statistika STIS, 2022)
The manufacturing sector is the first largest contributor to the Indonesian economy. However, the contribution of the manufacturing sector has always decreased from year to year. In fact, if a country wants to become a developed country, it is necessary to change the wrong economic structure related to the linkage of the secondary sector or sector industry. The industrial sector in Indonesia is dominated by provinces located in the Western Region of Indonesia (KBI). However, the productivity of the processing industry at KBI has always been below the Eastern Indonesia Region (KTI). The measure of productivity to describe all factors of production is the Total Factor Productivity (TFP). This study aims to calculate TFP, find out the general description of TFP, and analyze the factors that affect TFP in the processing industry at KBI. The calculation of TFP in the processing industry uses the Cobb-Douglas production function using a regression data panel with FGLS-SUR estimation. The results obtained from the provinces in KBI have TFP values ​​below the average. The analysis of variables that affect the processing of the TFP industry uses a regression data panel with the FGLS-SUR estimation model. It is found that wages and educated labor positively affect TFP and electricity use and exports negatively affect TFP.